2015
DOI: 10.1158/1541-7786.mcr-15-0014
|View full text |Cite
|
Sign up to set email alerts
|

Defective Myb Function Ablates Cyclin E1 Expression and Perturbs Intestinal Carcinogenesis

Abstract: Cyclin E1 is essential for the reentry of quiescent cells into the cell cycle. When hypomorphic mutant Myb mice (Myb Plt4 ) were examined, it was noted that Cyclin E1 (Ccne1) expression was reduced. Furthermore, the induction of Ccne1 in recovering intestinal epithelia following radiation-induced damage was ablated in Myb-mutant mice. These data prompted us to investigate whether Myb directly regulated Ccne1 and to examine whether elevated Myb in colorectal cancer is responsible for Cyclin E1-driven tumor grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In the present study, our data revealed the essential role of MYB in promoting the growth of PC cells under in vitro as well as in orthotopic tumour xenograft mouse model. Similar observations have also been made in other studies ( Melani et al , 1991 ; Ye et al , 2014 ; Cheasley et al , 2015 ; Wang et al , 2015 ). Blocking the function of MYB by antisense oligonucleotides or its dominant-negative forms led to the suppression of proliferation and survival in acute myeloid leukemia and chronic myeloid leukemia ( Jahagirdar et al , 2001 ; Pattabiraman and Gonda, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, our data revealed the essential role of MYB in promoting the growth of PC cells under in vitro as well as in orthotopic tumour xenograft mouse model. Similar observations have also been made in other studies ( Melani et al , 1991 ; Ye et al , 2014 ; Cheasley et al , 2015 ; Wang et al , 2015 ). Blocking the function of MYB by antisense oligonucleotides or its dominant-negative forms led to the suppression of proliferation and survival in acute myeloid leukemia and chronic myeloid leukemia ( Jahagirdar et al , 2001 ; Pattabiraman and Gonda, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in our recently published study, we reported that overexpression of MYB promoted, whereas its knockdown inhibited, the growth of prostate cancer cells ( Srivastava et al , 2012 ). More recently, Cheasley et al (2015) demonstrated that defective MYB function perturbs colorectal tumorigenesis in mouse model. Furthermore, an overexpression of MYB was also reported in nasopharyngeal carcinoma (NPC), which was associated with the growth of NPC cells ( Wang et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that upregulation of MYB increased the relative number of cells, which was consistent with previous findings in prostate and pancreatic cancer (37,38). Knockdown of MYB significantly inhibited cell proliferation, which was similar to findings for acute myeloid leukaemia, chronic myeloid leukaemia and colon cancer (39,40). Mechanistically, previous studies demonstrated that MYB induced the growth of tumour cells through the promotion of cell cycle progression, which was associated with cell proliferation (41,42).…”
Section: Discussionsupporting
confidence: 90%
“…This G1/S and G2/M cell cycle arrest is mediated through downregulation of cyclin E1 during G1/S transition (Ohtsubo et al, 1995, Malaterre et al, 2007, Cheasley et al, 2015 and cyclin B1 during G2/M transition (Nakata et al, 2007). Furthermore, five DNA damaging agents (ETO, cisplatin, doxorubicin, mitomycin C and hydroxyurea) cause S phase delay and G2/M phase arrest (Smith et al, 1994, Ling et al, 1996, Johnson et al, 1999, Kang et al, 2001, Nam et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that MYB knockdown inhibits cell proliferation and leads to cell cycle arrest at the late G1 or early S phase (Drabsch et al, 2007) via downregulation of cyclin B1 expression (Okada et al, 2002, Nakata et al, 2007 and cyclin E1 (Malaterre et al, 2007, Cheasley et al, 2015. MYB overexpression promotes cell cycle progression and cell proliferation through upregulation of cyclins (A1, D1 and E1) (Srivastava et al, 2012).…”
Section: 211) Pathway Analysesmentioning
confidence: 99%